2016
DOI: 10.1111/imj.12965
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence 1 month after hospital discharge in medical inpatients

Abstract: Non-adherence to prescription medications is suboptimal and consistent with previous overseas studies. Having a carer responsible for medications is associated with significantly lower rates of non-adherence. Understanding patients' preferences and involving them in their healthcare may reduce intentional non-adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 23 publications
0
20
0
3
Order By: Relevance
“…Interestingly, in our study, while comparing the patients’ characteristics between the two groups, the control group had significantly more carers helping with medication management. Additionally, having a carer responsible for administering medications was significantly associated with a better adherence rate in the control group . Foebel et al also found that presence of a caregiver at home significantly improves medication adherence for patients with heart failure and mild cognitive impairment .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Interestingly, in our study, while comparing the patients’ characteristics between the two groups, the control group had significantly more carers helping with medication management. Additionally, having a carer responsible for administering medications was significantly associated with a better adherence rate in the control group . Foebel et al also found that presence of a caregiver at home significantly improves medication adherence for patients with heart failure and mild cognitive impairment .…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, medical student‐led intervention is unique. This study is an extension of a previous study, which revealed that 39.7% of patients were not adherent to their medications 1 month after discharge from hospital . The aim was to assess the effectiveness of introducing a pre‐discharge medication education session led by a medical student, which included providing a written take home daily medication plan to improve adherence rates.…”
Section: Comparisons Of Patient Characteristics Between Control and Imentioning
confidence: 98%
See 1 more Smart Citation
“…Discharge letters provide general practitioners (GP) information about the patient's recent hospital admission, including investigations, results and the required follow‐up treatments and appointments; they are the most common form of communication between inpatient setting and outpatient care providers (Kripalani, Jackson, Schnipper, & Coleman, ). Trauma patients should be discharged home with the discharge letter, and instructions to visit their GP promptly after hospital discharge (Mitchell, Chong, & Lim, ). This practice ensures that the discharge letter is readily available at the first GP visit.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of medication non-adherence globally has been consistently reported to be between 20% and 50%. 12 Non-adherence is one of the biggest obstacles in prescribing as it can negatively affect health outcomes, clinician-patient relationships and the health budget. It is commonly associated with newly prescribed medications to treat chronic conditions such as hypertension, hyperlipidaemia and diabetes.…”
Section: Non-adherencementioning
confidence: 99%